The Role of Entrepreneurial Ecosystems in Fostering Startup Success and Innovation - Mittal, Vaidehi (Journal of Global Economy, Business and Finance, 2026)
It is evident that entrepreneurship thrives not in isolation but within dynamic ecosystems that foster innovation, investment, and collaboration. This paper explores the critical components that shape successful entrepreneurial ecosystems, including access to capital, talent acquisition, regulatory frameworks, mentorship networks, and infrastructure. By analyzing renowned hubs like Silicon Valley and Tel Aviv, the study highlights how these ecosystems fuel disruptive innovation and economic expansion. In my view, a well - structured entrepreneurial ecosystem not only enables startups to scale but also creates a feedback loop where successful ventures contribute to sustained growth. However, challenges such as funding gaps, talent retention issues, and regulatory barriers can stifle progress. This suggests that to maintain competitiveness, ecosystems must evolve continuously, ensuring long - term sustainability for startups. By addressing these challenges, stakeholders including policymakers, investors, and entrepreneurs can cultivate environments that nurture groundbreaking ideas and propel economic transformation.